Jagged Love: Narratives of Romance on Dating Apps during COVID-19. - Portolan, Lisa; McAlister, Jodi (Sexuality & Culture, 2022)
The romance plot is one of the most pervasive narratives in Western society. It is a cultural masterplot: a story with which almost everyone is familiar, which can deeply and intrinsically shape the way we think about how we live. This article examines how people interact with the romance masterplot and how it affects their search for love on dating apps in Australia during the global pandemic in 2020. Using data drawn from interviews and focus groups, and combining sociological research and narrative theory, we explore the way the romance masterplot affects the way people approach romance in dating apps, and how this has been complicated by the pandemic. We propose that participants use of dating apps in this period was characterised by 'jagged love', which we have theorised in relation to Zygmunt Bauman's notion of 'liquid love'. This manifested cyclically, as participants turned to the apps seeking the security offered by the romance masterplot in a time of global uncertainty; swiped, matched, and messaged in large numbers, and lost faith in the apps ability to deliver on the romantic masterplot. While episodic behaviour on dating apps is not new, the pandemic heightened and accelerated the process as people desperately sought the certainty offered by the romance masterplot, quickly lost faith because of the limitations of the pandemic, and then returned again.